1995
DOI: 10.1007/bf00797913
|View full text |Cite
|
Sign up to set email alerts
|

Transmural regulation of myocardial perfusion by neuropeptide Y

Abstract: In vivo studies have shown that sympathetic nerve stimulation improves the transmural distribution of myocardial perfusion by increasing the endocardial/epicardial flow ratio; however, the mechanism of this effect is unknown. During nerve stimulation both norepinephrine (NE) and neuropeptide Y (NPY) are released, either or both of which may exert vasoconstrictor effects. The present studies were performed to examine the effects of these two cotransmitters on the transmural distribution of myocardial perfusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
3
1
Order By: Relevance
“…These authors conclude that ␣ 1 -adrenoceptor-mediated coronary constriction limits oxygen delivery to the subendocardium and compromises myocardial contraction. Although the experimental conditions in Gwirtz et al's study differ from the present investigation, the detrimental effects of ␣-adrenoceptor vasoconstriction found by Gwirtz et al are not supported by the present results or the literature discussed above (2,12,16,17). The reason for the discrepancy is not apparent at this time.…”
Section: H2753contrasting
confidence: 93%
See 1 more Smart Citation
“…These authors conclude that ␣ 1 -adrenoceptor-mediated coronary constriction limits oxygen delivery to the subendocardium and compromises myocardial contraction. Although the experimental conditions in Gwirtz et al's study differ from the present investigation, the detrimental effects of ␣-adrenoceptor vasoconstriction found by Gwirtz et al are not supported by the present results or the literature discussed above (2,12,16,17). The reason for the discrepancy is not apparent at this time.…”
Section: H2753contrasting
confidence: 93%
“…The difference may be due to neuropeptide Y, which is coreleased with norepinephrine from sympathetic nerves. Gutterman and Morgan(12) observed that the coinfusion of neuropeptide Y with norepinephrine potentiated the norepinephrine effect of augmenting inner layer flow compared with outer layer flow in a preparation with adenosine-induced vasodilation. Norepinephrine infusion was used in the present experiment because it is not practical to obtain a long steady effect with electrical stimulation of sympathetic nerves while adjusting the aortic snare to match systolic blood pressure before and after ␣-adrenoceptor blockade.Adrenergic activation has been shown to decrease arterial compliance in vivo(3).…”
mentioning
confidence: 99%
“…Regional interruption of autonomic innervation occurs after myocardial infarction and may predispose the heart to arrhythmias and/or alterations in coronary flow, depending on the location and the overall extent of injury (1023). In general, sympathetic nerves release norepinephrine, neuropeptide Y, and ATP, while parasympathetic nerves release acetylcholine and vasoactive intestinal polypeptide (237, 351, 413, 422, 478, 817, 818). Studies by Brody and colleagues also provide seminal evidence of a role for central neural pathways in the regulation of coronary blood flow.…”
Section: Neural Controlmentioning
confidence: 99%
“…During resting conditions α-adrenoceptor activation has little effect on transmural flow distribution, because there is an adequately long diastolic period to fill intramyocardial capacitance and there is ample vasodilator reserve in the subendocardium [2, 6, 40]. However, when tachycardia is combined with high coronary flow caused by adenosine infusion [27, 40], dipyridamole [2], or exercise [37] α-adrenoceptor activation has a favorable effect on transmural flow distribution. These observations may explain the well-documented paradoxical α-adrenoceptor-mediated coronary vasoconstriction during exercise.…”
Section: Transmural Blood Flowmentioning
confidence: 99%